Elimination of Repeated Occurrences in Multimedia Search Engines - Alqaraleh, Saed; Ramadan, Omar (Zarka Private Univ, 2014)
In this paper, we have proposed a new method for eliminating repeated occurrences in multimedia search engines. We have built software that extracts information from multimedia databases which will compare these multimedia files and marks only one copy of repeated files. The developed software can work with any search engine and can also work in a routine manner to deal with any updates on the databases. Moreover, the software allows multiple copies to be executed in parallel and consequently it improves the efficiency of multimedia searching.
Keywords: Search engines; multimedia search engines; information retrieval